Nahdhatul Ulama and Muhammadiyah's Responses to the Religious Blasphemy in the Case of Non-Muslim Leader in Indonesia - Saadatul Jannah (Qur'an and Hadith Academic Society, 2018)
This study aims to examine how the ideological preferences of Islamic organizations such as Nahdhatul Ulama (NU) and Muhammadiyah (MU) affect the understanding of the Quran. Using a descriptive analytic method, the author discusses how NU and MU respond to cases of blasphemy on the leadership of religion Indonesian non-Muslims. This article finds that understanding the Quranic text goes hand in hand with the understanding of the ideology of each organization. The performative function of the Quran will also work as it should depend on the understanding that has been established within an organization.